Does Good Corporate Governance Strengthen the Link Between ESG Reporting and Financial Performance? A Study on the IDX ESG Leaders Index - Harahap, Dewi Rahma Nurliana; Akbar, Taufik (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The growing adoption of Environmental, Social, and Governance (ESG) practices in Indonesia is supported by regulatory pressure and rising awareness, yet evidence of their impact remains mixed. This study examines the effect of ESG disclosure on financial performance and firm value, and evaluates the moderating role of Good Corporate Governance (GCG) in non-financial firms listed in the IDX ESG Leaders index (2021–2024). Using ten purposively sampled firms (forty firm-year observations), ESG was measured with forty five item GRI index and GCG with seven governance indicators. Panel regression and Moderated Regression Analysis show ESG disclosure has insignificant effects on both financial performance and firm value, while GCG does not moderate these relationships. Findings highlight the early stage of ESG integration in Indonesia, emphasizing the need for improved disclosure quality and stronger governance mechanisms.